2012
DOI: 10.1371/journal.pone.0030231
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Consciousness and Cognition in Memory and Perception: Evidence for Both State and Strength Processes

Abstract: Subjective experience indicates that mental states are discrete, in the sense that memories and perceptions readily come to mind in some cases, but are entirely unavailable to awareness in others. However, a long history of psychophysical research has indicated that the discrete nature of mental states is largely epiphenomenal and that mental processes vary continuously in strength. We used a novel combination of behavioral methodologies to examine the processes underlying perception of complex images: (1) ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
125
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(138 citation statements)
references
References 43 publications
(62 reference statements)
12
125
0
1
Order By: Relevance
“…According to Aly and Yonelinas (2012), "state-based" perception is a discrete perceptual state that does either occur or not occur, and that is accompanied by conscious perception of details of the changing object. By contrast, "strength-based" change detection can vary from weak to strong and is accompanied by a feeling of knowing that something has changed, but with little to no ability to identify what the change was.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Aly and Yonelinas (2012), "state-based" perception is a discrete perceptual state that does either occur or not occur, and that is accompanied by conscious perception of details of the changing object. By contrast, "strength-based" change detection can vary from weak to strong and is accompanied by a feeling of knowing that something has changed, but with little to no ability to identify what the change was.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, "strength-based" change detection can vary from weak to strong and is accompanied by a feeling of knowing that something has changed, but with little to no ability to identify what the change was. Using receiver operating characteristics, Aly and Yonelinas (2012) demonstrated that both types of perceptual judgments contribute independently to change detection performance. In later studies, the authors demonstrated that hippocampal damage impairs strength-but not state-based scene perception, and that hippocampal activation measured in fMRI correlates with strength-based, but not state-based perception (Aly et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…Perception is often categorical (Harnard, 1987) and perceptual categorization can potentially affect decision making (Kiani et al, 2008;Aly and Yonelinas, 2012). Discrete categorization at the perceptual stage is at odds with the requirement that optimal decisions require evaluating the consequences of actions considering all possible states of the world-not just the state perceived.…”
Section: Discussionmentioning
confidence: 99%
“…This rule is similar to the Becker-DeGroot-Marshak mechanism in behavioral economics (Becker et al, 1964) and provides incentives for the subject to truthfully reveal a subjective probability p. For each of the 6 selected trials, subjects drew a ball from a bag of bingo balls labeled 1-100. If p Ͼ l 1 , the computer checked to see if the subject had correctly answered the relevant component of the task (selected direction for "Probability dots?," target acquisition for "Probability hit?," and overall success for "Probability overall?").…”
Section: Task and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation